Genome Wide Identification and Characterization of Apple WD40 Proteins and Expression Analysis in Response to ABA, Drought, and Low Temperature - Bo Zhang; Dong Qu; Huijuan Yang; Xiaogang Long; Zhenzhen Zhu; Yazhou Yang; Zhengyang Zhao (Horticulturae, 2022)
Basic WD40 proteins, which are characterized by a conserved WD40 domain, comprise a superfamily of regulatory proteins in plants and play important roles in plant growth and development. However, WD40 genes have been rarely studied in apple (Malus × domestica Borkh.). In this study, 346 WD40 genes classified in 12 subfamilies, were identified in the apple genome. Evolutionary analysis of WD40 proteins in apple and Arabidopsis revealed that the genes were classifiable into 14 groups, and the exon/intron structure of each group showed a similar structure. Analysis of collinearity showed that the large-scale amplification of WD40 genes in apple was largely attributable to recent whole-genome replication events. Nineteen candidate stress-related genes, selected by GO annotation and comparison with Arabidopsis homologs, showed different expression profiles in six organs at different developmental stages in response to exogenous abscisic acid (ABA), drought, and low temperature. Eight genes (MdWD40-17, 24, 70, 74, 219, 256, 283, and 307) showed a distinct response to one or more treatments (ABA, drought, and low temperature) as indicated by quantitative real-time PCR analysis. Taken together, these data provide rich resources for further study of MdWD40 genes and their potential roles in stress responses in apple.